2014
DOI: 10.1182/blood-2013-07-514372
|View full text |Cite
|
Sign up to set email alerts
|

Diverse T-cell responses characterize the different manifestations of cutaneous graft-versus-host disease

Abstract: Key Points• Distinct T-cell patterns characterize the acute and chronic forms of cutaneous GVHD.• Increased TSLP expression is an indicator of acute cutaneous GVHD development.Graft-versus-host disease (GVHD) is a major complication of allogeneic hematopoietic stem cell transplantation (HCT) and can present in an acute (aGVHD), a chronic lichenoid (clGVHD), and a chronic sclerotic form (csGVHD). It is unclear whether similar or different pathomechanisms lead to these distinct clinical presentations. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 47 publications
6
86
0
8
Order By: Relevance
“…Indeed, Annunziato et al previously showed that the Th1/Th17 subset showed increased cytotoxic capacity and lower susceptibility to the Treg suppressive activity (52). Comparably, Brüggen et al observed a mixed Th1/Th17 signature in the skin of patients with lichenoid cGvHD (32).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, Annunziato et al previously showed that the Th1/Th17 subset showed increased cytotoxic capacity and lower susceptibility to the Treg suppressive activity (52). Comparably, Brüggen et al observed a mixed Th1/Th17 signature in the skin of patients with lichenoid cGvHD (32).…”
Section: Discussionmentioning
confidence: 86%
“…In humans, there is a paucity of data. Dander et al showed an increase of Th17 cells in the blood of patients with active cGvHD (23), and a mixed Th1/Th17 signature was observed in the skin of patients with active disease (32). More recently, we identified candidate biomarkers (CCL14 and CD146) in the plasma of patients developing gastrointestinal (GI) GvHD that revealed an activated Th17-prone T cell population (CD4 + CD146 + CCR5 + T cells) participating in the pathogenesis of aGvHD (33).…”
Section: Introductionmentioning
confidence: 98%
“…In clinical cGVHD studies, increased IL-17 messenger RNA transcripts and significant Tc17 infiltration were demonstrated in skin, 72 whereas in the oral mucosa, Th17 infiltration dominated. Cytokines (IL-6, IL-21) known to support Th17 generation in GVHD are elevated in GVHD, [73][74][75][76] and STAT3, which drives Th17 development and Th17-dependent autoimmunity, 77 is essential for CD4 1 T-cell-mediated sclerodermatous cGVHD.…”
Section: T-cell Effector Mechanisms Driving Cgvhd Pathologymentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] Our previous report showed that B cells augmented Th17 expansion in the lung but not in the skin at 40 days after HCT. 15 Whether donor B cells and their antibodies affect Th17 expansion in the skin beyond 40 days after HCT has not been investigated.…”
Section: Cd8mentioning
confidence: 99%